Impact of Glissonean Pedicle Approach for Centrally Located Hepatocellular Carcinoma in Mongolia - Chinburen, Jigjidsuren (Int Surg, 2015)
Approaches to surgical resection of centrally located HCC remain controversial. Traditionally, hemi- or extended hepatectomy is suggested. However, it carries a high risk of postoperative complications in patients with cirrhosis. An alternative approach is Glissonean pedicle transection method. This study was conducted to assess the surgical and survival outcomes associated with central liver resection using the Glissonean pedicle transection. Sixty-nine patients with centrally located HCC were studied retrospectively. They were divided into conventional approach group with hemi- or extended hepatectomy, and Glissonean approach group with multisegmental central liver resection using the Glissonean pedicle transection. Glissonean pedicle transection method has comparable or superior surgical and survival outcomes to conventional hemi- or extended hepatectomy with regard to intraoperative bleeding, complications, hospital stay, and postoperative mortality and survival outcomes in patients with centrally located HCC. The 1-, 3-, and 5-year overall survival rates of the conventional approach group were 74%, 64%, and 55% respectively. For the Glissonean approach group, the 1 and 3-year overall survival rates were 86% and 61%, respectively. Glissonean pedicle transection method is a safe and effective surgical procedure in patients with centrally located HCC.